2006
DOI: 10.1007/11907466_25
|View full text |Cite
|
Sign up to set email alerts
|

CMDB – Yet Another MIB? On Reusing Management Model Concepts in ITIL Configuration Management

Abstract: Abstract. According to ITIL, a CMDB (Configuration Management Database), containing a logical model of the IT infrastructure, forms the basis for effective and efficient IT Service Management. However, a common understanding of what constitutes a CMDB has not yet been established. By contrast, concepts for building and using MIBs (Management Information Base) -also aimed at providing logical models of the IT infrastructure -have long since been established in the area of systems management.This paper presents … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2008
2008
2016
2016

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 15 publications
(9 citation statements)
references
References 4 publications
0
7
0
Order By: Relevance
“…This is why adaptability is an important requirement on an information model in the area of ITSM (cf. [12]) and should be considered during its design.…”
Section: Information and Data Modelingmentioning
confidence: 99%
See 1 more Smart Citation
“…This is why adaptability is an important requirement on an information model in the area of ITSM (cf. [12]) and should be considered during its design.…”
Section: Information and Data Modelingmentioning
confidence: 99%
“…al. [12], different information models from practice and research -among them the Common Information Model (CIM) and the Shared Information/Data Model (SID) -have been analyzed with respect to their capability to model ITIL information artifacts. The SID [13] has turned out as most promising, since SID has been developed to support and underpin eTOM's information artifacts and was the first information model tightly coupled to management processes.…”
Section: Information Modeling In Itsmmentioning
confidence: 99%
“…In 2006, Brenner and al. established a set of criteria for evaluate the possible reuse of CIM to build a CMDB [6]. They give a comprehensive overview of the criteria and illustrate how CIM fulfill these criteria.…”
Section: A Flexible Data Modelmentioning
confidence: 99%
“…As MIB is limited in describing a single system, a view of the entire infrastructure, including the relationships between its components, is not supported by the model. In practice, this gap is often filled by functionalities provided by SNMP-based network management tools which, for example, support the visualization of network topologies (Brenner et al, 2006). Aside from the fact that, in general, the research initiatives are committed to the use of technologies and tools, it is also observed that they are characterized by specific purposes in relation to peculiar applications in information systems that restrict their conceptualizations.…”
Section: It Service Configuration Managementmentioning
confidence: 99%